Exfoliation of layered mixed zirconium 4-sulfophenylphosphonate phenylphosphonates - Kopecká, Katerina; Melánová, Klara; Beneš, Ludvik; Knotek, Petr; Mazur, Michal; Zima, Vitezslav (Dalton transactions (Cambridge, England, 2020)
Mixed zirconium 4-sulfophenylphosphonate phenylphosphonates with formulae Zr(HO3SC6H4PO3)1.8(C6H5PO3)0.2·2.6H2O, Zr(HO3SC6H4PO3)1.3(C6H5PO3)0.7·2H2O, and Zr(HO3SC6H4PO3)0.7(C6H5PO3)1.3·3.6H2O (generally, ZrSPhP) were intercalated with a series of amino alcohols, H2N(CH2)nOH, where n = 2 to 6, and triethylamine. It was found that in the case of amino alcohols the basal spacing of the intercalates increases linearly with n. The intercalates prepared can be exfoliated either by sonication or by the action of high-shear forces. The use of a high-shear force disperser is a more efficient exfoliation method, as it provides lamellas with larger lateral dimensions in a much shorter time. It was found that amino alcohols provide roughly the same results regardless of the length of their carbon chain. As follows from atomic force microscopy measurements, triethylamine is the most appropriate exfoliation agent for ZrSPhP as it produces platelets with the largest lateral size and the lowest amount of defects.